2008
DOI: 10.1152/ajplung.00386.2007
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin attenuates release of neutrophilic and remodeling factors from primary bronchial epithelial cells derived from stable lung transplant recipients

Abstract: Obliterative bronchiolitis (OB), the major cause of chronic lung allograft dysfunction, is characterized by airway neutrophilia, inflammation, and remodeling, with progressive fibroproliferation and obliteration of small airways that ultimately leads to patient death. Statins have potential anti-inflammatory effects and have been demonstrated to confer a survival advantage in lung transplant patients. We postulated that the beneficial effects of simvastatin in lung transplantation are in part due to inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 55 publications
4
40
0
2
Order By: Relevance
“…Statins also prevent elastase-mediated emphysema in mice and are associated with evidence for proliferation and regeneration of alveolar epithelial cells [184]. At a cellular level, statins inhibit the effects of IL-17 and TGF-b in stimulating mediator release from primary airway epithelial cells, indicating their potential to modulate the inflammatory response and small airway fibrosis in COPD [185]. Statins also stimulate the uptake of apoptotic neutrophils by alveolar macrophages (efferocytosis), an effect that is mediated via inhibition of the prenylation and activation of RhoA, which is involved in the phagocytosis of apoptotic cells [186].…”
Section: Statinsmentioning
confidence: 99%
“…Statins also prevent elastase-mediated emphysema in mice and are associated with evidence for proliferation and regeneration of alveolar epithelial cells [184]. At a cellular level, statins inhibit the effects of IL-17 and TGF-b in stimulating mediator release from primary airway epithelial cells, indicating their potential to modulate the inflammatory response and small airway fibrosis in COPD [185]. Statins also stimulate the uptake of apoptotic neutrophils by alveolar macrophages (efferocytosis), an effect that is mediated via inhibition of the prenylation and activation of RhoA, which is involved in the phagocytosis of apoptotic cells [186].…”
Section: Statinsmentioning
confidence: 99%
“…Studies have shown that statins reduce neutrophil influx in the lung which might have a strong effect on attenuating the downstream inflammatory events, such as macrophage influx, lymphocyte activation and inhibition of cytokine release, in particular IL-8 that appears central to the neutrophil inflammation of the lung [67][68][69][70][71][72][73][74][75][76][77][80][81][82][83][84][85][86][87][88]. The inhibition of IL-6, IL-8 and GM-CSF expression by statins has been shown in cell cultures of human BEC [65,70]. Statins have also been shown to modify airway inflammation in animal models and matrix remodelling, notably inhibiting emphysema formation [73][74][75].…”
Section: Statin Effects On Pulmonary Inflammation In Copdmentioning
confidence: 99%
“…Further support for the protective role of statins on lung inflammation comes from lung transplant studies that show concomitant use of statins reduces post-transplant bronchiolitis and improves lung function compared to patients not receiving statins [70,76,82,121]. This is an inflammatorybased complication of lung transplantation with over lapping pathology with COPD, including small airway inflammation dominated by airway fibrosis (bronchiolitis obliterans).…”
Section: Statin Effects On Pulmonary Inflammation In Copdmentioning
confidence: 99%
“…IL-17 seems to be an important mediator of linking activated T cells to accumulation of neutrophils, although solid data on T helper cells and neutrophils are lacking. In vitro work confirmed that IL-17 orchestrated neutrophilic influx by the production of CXCL8 (IL-8), CXCL1 (GRO-a), and granulocyte-macrophage colony stimulating factor (GM-CSF) in airway epithelial cells, smooth muscle cells, endothelial cells, and fibroblasts (Murphy et al 2008). So, the importance of Th17 cells in neutrophilic inflammation lies in the ability of IL-17 to induce granulopoiesis, neutrophil chemotaxis, and the anti-apoptotic properties of G-CSF (Kolls and Linden 2004;Ouyang, Kolls, and Zheng 2008).…”
Section: )mentioning
confidence: 90%